2022
DOI: 10.1038/s41581-022-00618-4
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the kidney community: lessons learned and future directions

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected patients with kidney disease, causing significant challenges in disease management, kidney research and trainee education. For patients, increased infection risk and disease severity, often complicated by acute kidney injury, have contributed to high mortality. Clinicians were faced with high clinical demands, resource shortages and novel ethical dilemmas in providing patient care. In this review, we address the impact of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 162 publications
1
48
0
2
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic significantly affected individuals suffering from chronic medical conditions, such as chronic kidney disease (CKD), in terms of risk of infection, morbidity, and mortality [ 1 ]. Individuals suffering from CKD were reported to be at high risk of COVID-19 infection due to their dependence on in-center dialysis treatment, which is a high-risk environment for the transmission of COVID-19 infection [ 2 ]. Studies have also consistently shown that patients with CKD on hemodialysis carry an elevated risk of morbidity and mortality from COVID-19 [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic significantly affected individuals suffering from chronic medical conditions, such as chronic kidney disease (CKD), in terms of risk of infection, morbidity, and mortality [ 1 ]. Individuals suffering from CKD were reported to be at high risk of COVID-19 infection due to their dependence on in-center dialysis treatment, which is a high-risk environment for the transmission of COVID-19 infection [ 2 ]. Studies have also consistently shown that patients with CKD on hemodialysis carry an elevated risk of morbidity and mortality from COVID-19 [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…New or modified procedures and new methodologies/technologies in care processes have been incorporated for the clinical care of patients. Possibility of access, difficulty, or limitations for the implementation of these new methodologies/technologies, and acceptance/ adaptation by professionals and patients have shown a wide variety [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NIH also has a clinical trial underway to study if immune responses to vaccination improve when immunosuppression medication is temporarily reduced in the days leading up to and following vaccination (76,77). Though still unmatched to the general population, as boosters became available in the US, data shows that additional mRNA inoculations increase antibody titers for the majority of solid organ transplant patients (78,79).…”
Section: Vaccination Policies: History Present and Solutions Historymentioning
confidence: 99%